Deepfakes and Fact-checking: Influence of AI on the Disinformation Ecosystem from the Perspective of Fact- checkers and Academics - García-Marín, David; Noain-Sánchez, Amaya; Salvat-Martinrey, Guiomar (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
This study aims to analyse the uses and impact of artificial intelligence—particularly deepfakes—in disinformation campaigns, as well as the utility and potential of this technology in combating disinformation. Semi-structured interviews were conducted with 16 fact-checkers and experts in AI and disinformation in the Spanish context, and the data were analysed using grounded theory. The findings highlight how deepfakes play both a symbolic and an operational role in the disinformation ecosystem. Their influence extends beyond the generation of disinformation to affect the broader social perception of reality through strategies such as false-flag marketing and phenomena including the liar’s dividend and enshittification.